Anthropogenic stressors and riverine fish extinctions. (August 2017) - Dias, Murilo S.; Tedesco, Pablo A.; Hugueny, Bernard; Jézéquel, Céline; Beauchard, Olivier; Brosse, Sébastien; Oberdorff, Thierry
Highlights: Fish extinctions in Europe and the USA are analyzed against anthropogenic threats. Current extinction rates are ∼112 times higher than background extinction rates. Extinctions concern both diadromous and resident species. River fragmentation and exotic species partially explain fish extinctions. Dataset limitations may explain the weak explanatory power of the models. Abstract: Human activities are often implicated in the contemporary extinction of contemporary species. Concerning riverine fishes, the major biotic and abiotic threats widely cited include introduction of non-native species, habitat fragmentation and homogenization in stream flow dynamics due to the damming of rivers, dumping of organic loadings, degradation of the riverine habitat by agricultural practices and water abstraction for human and agricultural consumption. However, few studies have evaluated the role of each of these threats on fish extinction at large spatial scales. Focusing on Western Europe and the USA, two of the most heavily impacted regions on Earth, we quantify fish species loss per river basin and evaluate for the first time to what extent, if any, these threats have been promoting fish extinctions. We show that mean fish extinction rates during the last 110 years in both continents is ∼112 times higher than calculated natural extinction rates. However, we identified only weak effects of our selected anthropogenic stressors on fish extinctions. Only river fragmentation by dams and percentage of non-native species seem to be significant, although weak, drivers of fish species extinction. In our opinion, the most probable explanation for the weak effects found here comes from limitations of both biological and threats datasets currently available. Obtaining realistic estimates on both extinctions and anthropogenic threats in individual river basins is thus urgently needed.